PRODUCTION OF CALIBRATION GAS MIXTURES IN THE REPUBLIC OF KAZAKHSTAN - V. . Aleksandrov; A. . Nasibulina (Стандартные образцы)
The article presents the information about production of reference materials for composition of calibration gas mixtures in the Republic of Kazakhstan -creation, existing capabilities and development prospects